Chromatin architecture and alterations in the control of gene regulation - Hansen, Jeffrey (Henry Stewart Talks, 2007)
The chromatin environment, Hierarchical organization of chromatin fibers within interphase chromosomes, Milestone experiments that linked chromatin architecture and gene expression, Proteins and processes that influence both chromatin fiber architecture and gene expression, Core histone N-terminal tail domains, Core histone sequence variants, Linker histones, Heterochromatin proteins, Histone post-translational modifications, The structurally dynamic nature of the genome in vivo and its relation to gene expression
Reviewed at 2016/01/19